PEMBERHENTIAN ANGGOTA DPRD KARENA PINDAH PARTAI POLITIK DALAM PERSPEKTIF KEADILAN - Reski; Ardiansah; Winstar, Yelia Nathassa (Collegium Studiosum Journal, 2025)
Article 28E paragraph (3) of the 1945 Constitution of the Republic of Indonesia explicitly states that "every person shall have the right to freedom of association, assembly, and expression." The right to associate should not be narrowly interpreted as applying only to the general public but must also include the rights of politicians or members of parliament to freely determine their political affiliations and stances. Therefore, when someone chooses to switch parties for ideological, ethical, or constituent-related reasons, such action is constitutionally protected. Upholding dismissal solely on the basis of party-switching, as affirmed by the Constitutional Court, indirectly restricts citizens’ constitutional rights to associate, potentially amounting to a systemic human rights violation, carried out through legal mechanisms that ought to protect individual freedoms. The purpose of this research is to analyze the legal provisions regarding the dismissal of regional legislative council (DPRD) members who change political parties according to Indonesian legislation, and to evaluate whether such dismissal reflects the principle of justice for all parties involved. The method employed in this study is normative legal research. Based on the research findings, it is evident that the legal provisions for the dismissal of DPRD members who switch parties are regulated in several legislative instruments in Indonesia. The main legal basis is found in Law Number 23 of 2014 concerning Regional Government, reinforced by Law Number 7 of 2017 concerning General Elections, and rulings of the Constitutional Court (MK). These provisions are controversial as they potentially conflict with Article 28E paragraph (3) of the 1945 Constitution, which guarantees every citizen the right to association, assembly, and expression. Thus, while positive law grants political parties the legal right to dismiss their members who switch parties, from a normative and constitutional perspective, this remains a contentious issue in the context of human rights and the principles of a rule-of-law state. The dismissal of DPRD members for switching parties may reflect the principle of justice when viewed through the lens of procedural and substantive justice. In the context of positive law, such action is often justified as fair treatment toward political parties that feel disadvantaged by a legislator switching parties after winning a seat. According to this logic, parties believe they have the right to reclaim the political mandate, as the legislative seat is legally considered the property of the party. However, when viewed through the lens of justice theory, especially John Rawls’ concept of justice as fairness, such action is not necessarily substantively just. Rawls asserts that justice requires a balanced protection of each individual’s basic rights, and systems must be arranged to be as fair as possible to all parties—particularly to those who are least advantaged. In this context, a DPRD member dismissed for switching parties is exercising their constitutionally protected freedom of association and expression. If justice is assessed solely from the party’s perspective, then substantive justice for the DPRD member and the constituents they represent is overlooked. Therefore, even though the dismissal of DPRD members for party-switching has a normative legal basis, from a justice perspective, such actions may not reflect genuine justice for all parties. Voters and the DPRD members as political individuals may be harmed if such decisions are made without comprehensive consideration of their rights and voices.